Problematika Perkawinan di Bawah Umur Dalam Perspektif Hukum Perkawinan Islam di Indonesia - Ahmad Sibawai (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2024)
This study aims to: 1) analyze the problems of underage marriage from the perspective of Islamic marriage law in Indonesia, 2) understand the relevance of the regulation of the marriage age limit in national law to the principles of Islamic law. The research method used is normative legal research with a statutory approach and a conceptual approach. The legal materials for this study consist of primary legal materials, secondary legal materials, and tertiary legal materials. The legal materials were analyzed using legal interpretation methods, legal theories, and legal principles. The results of the study indicate that although Islamic law does not specify a numerical marriage age limit, the principle of maturity reflected in the concepts of baligh and rusyd emphasizes the importance of individual readiness to carry out household responsibilities. In addition, the regulation of the marriage age limit in national law aims to provide legal certainty and protect prospective couples from the risks of early marriage. Thus, this regulation is essentially in line with the principle of maqāṣid al-syarī‘ah which emphasizes the benefit and protection of individuals in family life.